Strategi Pemasaran Cinema XXI dalam Mempertahankan Dominasi Pasar Bioskop di Indonesia - Dewi Martha; Ira Meike Andariyani; Alfi Syukria (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to identify and analyze Cinema XXI's marketing strategies in maintaining its cinema market dominance in Indonesia amidst the disruption of digital streaming platforms post-pandemic. The research method employed is descriptive qualitative. Primary data were gathered through semi-structured interviews with Cinema XXI management in Jakarta and Karawang, as well as regular customers, complemented by field observations and data triangulation techniques. The results indicate that Cinema XXI successfully maintains its market hegemony through the integrated execution of five online-to-offline (O2O) strategic pillars. First, social media marketing effectively triggers digital buzz and increases engagement by up to 30%. Second, experiential marketing through premium facilities such as IMAX theaters, Dolby Atmos, and recliner seats successfully delivers an immersive value-added experience that home entertainment cannot replicate. Third, the loyalty program directly contributes to repeat visit frequency, although the point redemption mechanism requires simplification. Fourth, omnichannel implementation via the m.tix application successfully mitigates transactional friction and boosts customer loyalty by up to 40%. Fifth, marketing innovations, including thematic film festivals and Virtual Reality (VR) technology, are effective in sustaining brand relevance among the younger generation.